Facile fabrication and photoelectrochemical properties of a CuO nanorod photocathode with a ZnO nanobranch protective layer. Issue 105 (28th October 2016) - Shaislamov, Ulugbek; Krishnamoorthy, Karthikeyan; Kim, Sang Jae; Chun, Wongee; Lee, Heon-Ju
Abstract : Photoelectrochemical properties of CuO/ZnO photoelectrodes fabricated with nanorod and film structures were investigated and the effect of surface morphology on their photoelectrochemical performance was discussed in detail. Abstract : In this study, the photoelectrochemical properties of CuO/ZnO photoelectrodes fabricated with nanorod and film structures were investigated and compared, and the effect of surface morphology on their photoelectrochemical performance was discussed in detail. The experimental results demonstrated that the CuO/ZnO photoelectrode with nanorod structures showed superior photoelectrochemical properties compared to that of the photoelectrode with the film structure. The electrochemical impedance analysis and UV-vis spectroscopy results confirmed that the hierarchical nanorod-like structure of the CuO/ZnO photoelectrode was advantageous for effective light absorption, and reduced charge transfer resistance at the electrode/electrolyte interface. At the same time, the ZnO layer effectively contributed to the suppression of photocorrosion in the CuO, and the photoelectrodes with a ZnO layer demonstrated 82.13% better stability in photoelectrochemical conditions.